(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Train transportation has become an essential part of everyone’s daily lives. Travelling from one location to another is easier using this train system. In recent years, train transportation in the Philippines has lacked innovation. The construction of the Superconducting Magnetic Train may benefit passengers and the environment. This study aims to reduce derailment incidents and promote safety and fast passenger travel. The research design used for the study was quantitative experimental research while utilizing a purposive sampling technique. The statistical treatment used for this study was a T-test to determine the difference between the two groups of respondents. Using a questionnaire as the research instrument, the researchers surveyed to identify the model’s acceptance level regarding construction materials, designs, mechanisms, and presentation. The study’s respondents are 3 Electrical Engineers and 3 Mechanical Engineers. The following procedures were undertaken in applying the superconducting magnet as an additive to normal training: Collect and prepare the materials and tools. Start by removing the outer layer of the copper wire using scissors. To form a spiral, wrap the copper wire around the pipe tube. Then, make a station model using popsicle sticks. Place the shaped copper wire on the plywood and station, then fix it. After that, place the neodymium magnet on both sides of the battery. Lastly, place the positive charge of the battery inside the spiral copper wire with the magnet. The study results regarding construction materials, designs, mechanisms, and presentation are Strongly Accepted. The overall mean of the Electrical Engineers was 4.42, interpreted as Moderately Accepted, and Mechanical Engineers had an overall mean of 4.97, interpreted as Strongly Accepted. The T-value was 2.776, and the T-computed was -2.716. It indicates a significant difference between the assessments of the two groups of respondents. To further improve the study, the respondents recommend adding more rolled copper wire and making a curved path to test if the battery attached to a magnet can get through it.